Streaming towards innovation: Understanding consumer adoption of OTT services through IRT and TAM - Aruna Polisetty; G Sowmya; Subhajit Pahari (Cogent Business & Management, 2023)
The rise of cord-cutting due to technological advancements and internet accessibility has led to an increased interest in understanding the adoption behavior of consumers towards over-the-top services (OTTs). This study aimed to comprehend the barriers to adopting the first wave of OTTs and the innovation characteristics, along with the propagation mechanism, in the second wave, using the Innovation Resistance Theory (IRT) and the Technology Acceptance Model (TAM), respectively. The study was conducted in India, with 302 and 572 respondents for the first and second waves, respectively. Data were analyzed through confirmatory factor analysis and structural equation modeling. The findings revealed that value barriers, technology vulnerability barriers, and individual barriers had the highest impact on consumer resistance, negatively impacting continued usage intention. Consumer habits were found to play a conditional role in antagonizing the effects of consumer resistance on continued usage intention. In the second wave, innovation and consumer characteristics had no significant impact on continued usage behavior. Instead, a robust propagation mechanism was explored to overcome consumer resistance and promote innovation. These findings provide valuable insights for OTT service providers and policymakers to promote continued usage intention and overcome consumer resistance.
Keywords: 650; consumer adoption; Innovation Resistance Theory; over-the-top services; propagation mechanism; technology; Technology Acceptance Model